Non-small cell lung cancer (NSCLC): characteristics, risk factors, molecular profile patterns, and treatment — a retrospective cohort study from Palestine - Abdallah Damin Abukhalil; Khaldieh Mansour; Wardah Alhaj; Inas Salah; Yousef Sahoury; Ni’meh Al-Shami; Mohammad Qawasmeh (Journal of the Egyptian National Cancer Institute)
Abstract Introduction and background Non-small cell lung cancer (NSCLC) is the third most common type of cancer in Palestine and has the highest mortality rate. Treatment approaches for NSCLC depend on many factors including stage, histology, molecular profile, and patient performance status. Objectives This study explored the patient characteristics, molecular profiles, metastatic sites, prognosis, and treatment modalities. Methods This observational retrospective cohort study was conducted at multiple Palestinian hospitals. This study included patients diagnosed with metastatic NSCLC between 2016 and 2022. Patients with small-cell lung cancer (SCLC), newly diagnosed lung cancer, or incomplete information were excluded from the study. Patient data were obtained from the date of lung cancer diagnosis until death or loss to follow-up. Data were analyzed using IBM SPSS, and overall survival was calculated using the Kaplan–Meier estimate. Results The study included 102 patients, 80.4% were male, 40.2% were current smokers, 42.2% were ex-smokers, and 17.6% were nonsmokers. (86.35%) of the patients were diagnosed with adenocarcinoma, and (77.5%) were diagnosed with stage IV NSCLC. Tumor recurrence was observed in 47.1% of patients after surgery. A total of 56.9% had PDL-1 expression ≥ 10%, and 45.1% had EGFR mutations. Fourteen (13.7%) received mono-chemotherapy with an estimated OS of (1219.200) days, 34 (33.3%) received mono-immunotherapy with an estimated OS of (720.152) days, and 54 (52.9%) received a combination of chemotherapy and immunotherapy with an OS of 2006.777 days. PFS (> 1 year) was higher in patients receiving combination therapy (58.3%). Myelosuppression, renal damage, and liver damage are some of the major side effects experienced by patients receiving either type of treatment. Conclusion The findings of this study provide vital information on tumor molecular mutation patterns and PDL expression for the adoption of appropriate measures in prevention and treatment strategies for NSCLC in Palestine. The majority of patients diagnosed with NSCLC were males with a history of smoking and were diagnosed at an advanced stage, which requires increased education, wariness of lung cancer, and smoking cessation programs at the national level.